Electroacupuncture for tapering off long-term benzodiazepine use: study protocol of randomized controlled trial - Wing-Fai Yeung; Ka-Fai Chung; Zhang-Jin Zhang; Wai-Chi Chan; Shi-Ping Zhang; Roger Man-Kin Ng; Connie Lai-Wah Chan; Lai-Ming Ho; Yee-Man Yu; Li-Xing Lao (BMC, 2017)
Abstract Background Conventional approaches for benzodiazepine tapering have their limitations. Anecdotal studies have shown that acupuncture is a potential treatment for facilitating successful benzodiazepine tapering. As of today, there was no randomized controlled trial examining its efficacy and safety. The purpose of the study is to evaluate the efficacy of using electroacupuncture as an adjunct treatment to gradual tapering of benzodiazepine doses in complete benzodiazepine cessation in long-term benzodiazepine users. Methods/Design The study protocol of a randomized, assessor- and subject-blinded, controlled trial is presented. One hundred and forty-four patients with histories of using benzodiazepines in ≥50% of days for more than 3 months will be randomly assigned in a 1:1 ratio to receive either electroacupuncture or placebo electroacupuncture combined with gradual benzodiazepine tapering schedule. Both experimental and placebo treatments will be delivered twice per week for 4 weeks. Major assessments will be conducted at baseline, week 6 and week 16 post-randomization. Primary outcome is the cessation rate of benzodiazepine use. Secondary outcomes include the percentage change in the doses of benzodiazepine usage and the severity of withdrawal symptoms experienced based on the Benzodiazepine Withdrawal Symptom Questionnaire, insomnia as measured by the Insomnia Severity Index, and anxiety and depressive symptoms as evaluated by the Hospital Anxiety and Depression Scale. Adverse events will also be measured at each study visit. Discussion Results of this study will provide high quality evidence of the efficacy and safety of electroacupuncture as an adjunct treatment for benzodiazepine tapering in long-term users. Trial registration ClinicalTrials.gov NCT02475538 .